PENGIRAAN POSE MODEL MANUSIA PADA REPETISI KEBUGARAN AI PEMOGRAMAN PYTHON BERBASIS KOMPUTERISASI - muchlis abdul muthalib; Irfan Irfan; Kartika Kartika; Selamat Meliala Selamat Meliala (Universitas Majalengka, 2023)
Pandemic people don't have free access to Gym. The importance of keeping the body fit. This can be overcome with the Human Pose Estimation Computer Vision technique. Optimum and maximum distance testing data. Webcam detects movement and test data on AI Fitness Counter models. Human Pose Estimation detection data is taken when someone does fitness exercises such as pull ups, pushups, and lifting weights. Optimal webcam detects Human Pose Estimation model AI Fitness Counter is three meters. Every detail of the landmarks in the pose corresponds to the key points of each limb and the utility lines that connect form the skeleton of the body. The application of the number of detection repetitions takes advantage of the angle of the elbow when it is straight and when it is bent. The angle forms 300 then a stage up occurs and is counted as one repetition. Meanwhile, when the angle forms 1700, a stage down occurs, and one repetition is counted as well. The use of Media pipe for the detection results is accurate and effective. This detection was successful because all members of the body were detected.